The power of parties - Jon H. Fiva; Olle Folke; Rune J. Sørensen (Center for Economic Studies and ifo Institute (CESifo), 2013)
As with the market for goods and services, democratic competition involves political parties offering their services (policy programs) to citizen-consumers who vote for their preferred partisan supplier. Little is known about the partial effect of a shift in parties' seat shares for given voter preferences, particularly in proportional representation systems. We estimate party effects using a regression discontinuity design tailored to proportional systems. Based on rich local government data, the analyses show that parties matter for fiscal policies. A larger left-wing party leads to more property taxation and higher user charges. It also leads to higher spending on child care but less on old-age care. These effects are caused both by changes in the representation of individual parties and by shifts between the party blocs.
Keywords: C23; D72; H71; H72; 330; fiscal policy; proportional representation; regression discontinuity design